Museum exhibition planning and design - Bogle, Elizabeth (AltaMira Press, 2013)
Great exhibits are never an accident. Planning effective exhibits is a demanding process that requires the designer to consider many different aspects and navigate numerous pitfalls while moving a project from concept to reality. In Museum Exhibition Planning and Design, Elizabeth Bogle offers a comprehensive introduction and reference to exhibition planning and design. This book focuses on both the procedural elements of successful planning, like the phases of exhibit design and all associated tasks and issues, and on the design elements that make up the realized exhibit itself, such as color, light, shape, form, space, and building materials.This helpful guide includes:Breakdown of the design and development project phases used by professional planner/designersPrinciples of good design as they pertain to: color, light, shape, form, space, line, balance, accent, rhythm, proportion, and scaleCriteria to evaluate an exhibit and measure its success Discussion of construction contracts and proceduresDiscussion of building materials and their advantages and disadvantagesGlossary of museum and design terms for easy referenceBogle has translated her years of experience as an exhibition planner into a guide for practitioners of all sizes and levels of experience. For the solo practitioner, perhaps working with limited or no staff in a small institution, Bogle walks through every task that will be faced as the project develops. For the staff member of a larger institution or firm, this book serves as a checklist, reinforcing the instruction that comes from peers and previous experience. Museum Exhibition Planning and Design is a useful tool for anyone interested in or involved in bringing their exhibits to life.